Perbedaan Mobilisasi Dini 6 Jam dan 8 Jam Terhadap Peristaltik Usus Pada Pasien Post Operasi Dengan anastesi Umum di RS. dr. R. Soeprapto Cepu - Purnomo, Heru; Mu'awanah, Mu'awanah; Mudhofar, Mohammad Nur (Jurnal Studi Keperawatan, 2020)
ABSTRACTBackground : Early mobilization is some effort to defend autonomy as early as possible by guiding the victim for defending fisiologis function (Carpenito, 2001).  According Smeltzer Bare (2002) in patient with colon inflammation disturbance, explained that change position encourage doing passive and active exercise to depend muscle and prevent tromboembolic.  Activity limitation changed suitable with daily necessary.  General anesthesia can cause decreasing colon movement with stimuli parasympatic obstruction in colon muscle.  Client with local anesthesia will experience same case.  Direction surgery which involved intestinal can cause stopping intestinal while movement. Surgery action with general anesthesia in RS.DR.R.Soeprapto Cepuoften was being done in juny – December 2012 period reported 166 cases.Objective : This study to determine the difference of early mobilization 6 hours and 8 hours toward intestine peristaltic on post operation patient with general anesthesia at RSUD dr. R. Soeprapto Cepu. Methods : Method of this research  used quasi eksperimental design and taking sampling method was stratified random sampling, research was done into 20 respondences.  Collecting data technique using observation technique.  Statistic analysis used Independent t-test exam, organize and data analysis with computer program assist SPSS for windows 16.Result : The result analysis was shown with independent t-test exam was be found t hitung 0,662, t table 2,101, p value 0,641.  Where is t hitung t table (0,662 2,101) and p value alpha (0,641 0,05) above can be conclude Ho was accepted.  Its mean its’nt difference early mobilization 6 hours and 8 hours about peristaltic of intestine for post operation patient with general anesthesia in dr.R.Soeprapto Cepu Hospitals.Conclusion : Advice we recommend early mobilization of patients immediately after surgery with general anesthesia, according to the results of this study was able to mobilize patients early in the post anesthesia 6 hours. Keywords: mobilisation, peristaltic of intestine, post operation, general anesthesia.